Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0144956
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of a Killer Whale (Orcinus orca) Population’s Diet Using Sequencing Analysis of DNA from Feces

Abstract: Estimating diet composition is important for understanding interactions between predators and prey and thus illuminating ecosystem function. The diet of many species, however, is difficult to observe directly. Genetic analysis of fecal material collected in the field is therefore a useful tool for gaining insight into wild animal diets. In this study, we used high-throughput DNA sequencing to quantitatively estimate the diet composition of an endangered population of wild killer whales (Orcinus orca) in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 35 publications
5
76
0
Order By: Relevance
“…In their killer whale study, Ford et al. () analysed known percentages of DNA extracted from four fish species and the RRA of each fish corresponded well to input (generally within 5% of expected values) providing confidence in their conclusions. Using prey species of harbour seals, Thomas, Deagle, Eveson, Harsch, and Trites () carried out a detailed study on sequence recovery from blended tissue mixtures.…”
Section: Does Rra Actually Reflect Food Biomass?mentioning
confidence: 87%
See 3 more Smart Citations
“…In their killer whale study, Ford et al. () analysed known percentages of DNA extracted from four fish species and the RRA of each fish corresponded well to input (generally within 5% of expected values) providing confidence in their conclusions. Using prey species of harbour seals, Thomas, Deagle, Eveson, Harsch, and Trites () carried out a detailed study on sequence recovery from blended tissue mixtures.…”
Section: Does Rra Actually Reflect Food Biomass?mentioning
confidence: 87%
“…This effect can be illustrated in metabarcoding data from a population‐level diet study of killer whales (Figure ). This study concluded that the whale population's diet consisted primarily of Chinook salmon (~80%) based on high RRA of this species in most samples (Ford et al., ). If we consider the killer whales’ diet as occurrence (POO; each food species occurrence given equal value), the view changes considerably because other salmon species and halibut frequently detected at low levels become important prey.…”
Section: Does Converting Read Counts To Occurrence Data Solve Our Promentioning
confidence: 96%
See 2 more Smart Citations
“…Reduced diversity in these stocks has likely reduced the ecosystem's hatchery portfolio, and it is hypothesized that this could have a destabilizing effect on recruitment (Sturrock et al 2019). Maintaining diversity-and the stability it may confer-in the composite of Chinook stocks along the west coast of North America could be a critical factor for the recovery of southern resident killer whales, which depend heavily on Chinook salmon for prey (Ford et al 2016). Thus, other regions along the west coast that provide large contributions of hatchery Chinook salmon (e.g., Columbia River, Washington, and Oregon coast) might consider the findings presented in this study relevant, as future hatchery practices are designed.…”
Section: Discussionmentioning
confidence: 99%